2020
DOI: 10.7554/elife.50986
|View full text |Cite
|
Sign up to set email alerts
|

The CHORD protein CHP-1 regulates EGF receptor trafficking and signaling in C. elegans and in human cells

Abstract: The intracellular trafficking of growth factor receptors determines the activity of their downstream signaling pathways. Here, we show that the putative HSP-90 co-chaperone CHP-1 acts as a regulator of EGFR trafficking in C. elegans. Loss of chp-1 causes the retention of the EGFR in the ER and decreases MAPK signaling. CHP-1 is specifically required for EGFR trafficking, as the localization of other transmembrane receptors is unaltered in chp-1(lf) mutants, and the inhibition of hsp-90 or other co-chaperones d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…We next used A431 epidermoid carcinoma cells, which overexpress EGFR and strongly respond to EGF stimulation by forming filopodia in a MAPK-dependent manner (Haag et al, 2020; Van de Vijver et al, 1991). Since filopodia formation is difficult to assess quantitatively, we categorized cellular morphologies into three classes; 0 for cells without filopodia, 1 for cells with small filopodia covering part of the cortex, and 2 for cells with long filopodia covering most of the cortex ( Figure S8A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next used A431 epidermoid carcinoma cells, which overexpress EGFR and strongly respond to EGF stimulation by forming filopodia in a MAPK-dependent manner (Haag et al, 2020; Van de Vijver et al, 1991). Since filopodia formation is difficult to assess quantitatively, we categorized cellular morphologies into three classes; 0 for cells without filopodia, 1 for cells with small filopodia covering part of the cortex, and 2 for cells with long filopodia covering most of the cortex ( Figure S8A ).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were seeded at 80’000 cells/ml density in DMEM medium with or without supplements. After 32 hours, cells were exposed to thymidine (1:50) to arrest the cell cycle as described in Haag et al, 2020 (first thymidine block). 16 hours after, the first thymidine block was released by replacing the medium.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The downregulation of CHORDC1 has been shown to promote the interaction between ROCKII and NPM to result in an increase in ROCKII kinase activity, which leads to centrosome amplification [14]. CHORDC1 also ensures the localization of the tyrosine kinase receptor EGFR to the plasma membrane, which in turn regulates EGFR activity and EGF-induced actin cytoskeleton remodeling [15]. Additionally, there exists a novel ADP-dependent HSP90 interaction with the CHORDC1 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Inside the cells, Morgana regulates signal transduction by binding and inhibiting Rho kinases I and II ( Ferretti et al, 2010 ; Fusella et al, 2014 ) and promotes NF-kB activation ( Fusella et al, 2017 ). It is also involved in microtubule polymerization ( Palumbo et al, 2020 ), EGF receptor trafficking ( Haag et al, 2020 ), and extracellular vesicle secretion ( Urabe et al, 2020 ). We recently found that Morgana is secreted by several cancer cells through an unconventional pathway and it associates with HSP90 in the extracellular milieu.…”
Section: Ehsp90 Complexes Activate Cancer Cell Surface Receptorsmentioning
confidence: 99%